Meteorology Today: An Introduction to Weather, Climate and the Environment, 12th Edition - C. Donald Ahrens; Robert Henson (Cengage Learning, 2018)
METEOROLOGY TODAY: AN INTRODUCTION TO WEATHER, CLIMATE AND THE ENVIRONMENT by meteorologists C. Donald Ahrens and Robert Henson combines the latest in weather, climate and earth science to introduce students to the concepts and current issues of meteorology. Grounded in the scientific method, the new edition of this highly visual text shows students how to observe, calculate and synthesize information as budding scientists. Specific discussions center on severe weather systems like tornadoes and hurricanes, as well as everyday elements like wind, precipitation and the seasons.